2018
DOI: 10.1002/ls.1428
|View full text |Cite
|
Sign up to set email alerts
|

The purification and tribological property of the synthetic magnesium silicate hydroxide modified by oleic acid

Abstract: Modified magnesium silicate hydroxide (MMSH) nanoparticles were synthesised hydrothermally using MgO and SiO 2 as precursors and oleic acid as modification agent under alkaline condition. The tribological performances of MMSH as lubricant additives were studied. The X-ray diffraction and Fourier transform infrared spectroscopy spectra show that the synthetic MMSH nanoparticles contain no Mg (OH) 2 impurity and belong to the serpentine group. The tribological tests indicate that both MMSH and magnesium silicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The two-dimensional materials mainly include graphene [116], boron nitride [117], MoS 2 [118], and other 2D materials [119][120][121]. The other materials concentrate on metallic or nonmetallic nanoparticles [122,123], metallic or nonmetallic oxides [124,125], and inorganic nanocomposites [126]. Therefore, this section is divided into two parts, namely two-dimensional materials and other dimensional materials.…”
Section: Inorganic Additivementioning
confidence: 99%
“…The two-dimensional materials mainly include graphene [116], boron nitride [117], MoS 2 [118], and other 2D materials [119][120][121]. The other materials concentrate on metallic or nonmetallic nanoparticles [122,123], metallic or nonmetallic oxides [124,125], and inorganic nanocomposites [126]. Therefore, this section is divided into two parts, namely two-dimensional materials and other dimensional materials.…”
Section: Inorganic Additivementioning
confidence: 99%
“…Chang et al 20 reported that the synthesised MSH can form amorphous DLC films containing SiO x on the surface. Gao et al 18 confirmed that MSH was able to generate a self‐repairing layer containing iron oxides, silicon oxides, graphite, and Fe 3 C in a fourball friction test. However, the microstructure of the self‐repairing layer is rarely directly observed, and its self‐repairing mechanism is still unclear, especially under actual working conditions, which need to be further clarified.…”
Section: Introductionmentioning
confidence: 94%
“…However, except to magnesium silicate hydroxide (MSH,Mg 3 [Si 2 O 5 ](OH) 4 ), natural serpentine also contains different amounts of calcium oxide, aluminium oxide and iron oxide 17,18 . Moreover, the composition and morphology of serpentine in different regions are different.…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage, our group has studied the synthesis of MSH at different temperatures and reaction times and good tribological properties are obtained when MSH is used as lubricant additive [15]. Moreover, its tribological properties are further advanced by combining it with carbonaceous materials, such as graphene [16], oleic acid [17][18][19], PTFE [20], gelatin [21,22], and glucose [23]. However, the dispersion stability properties of MSH and its derivatives still need to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%
“…The base oil PAO10 is from Sinopec Research Institute of Petroleum Processing, and its parameters can be found from Ref. [19]. Other chemicals are listed in Table 1 which are all of the analytic grades.…”
Section: Introductionmentioning
confidence: 99%